Full-Dress Rehearsals with Actual Non-Infected Patients Builds Confidence and Familiarity – An Experience from Singapore during the COVID-19 Pandemic. Issue 1 (2nd January 2022) - Koh, Frederick H.; Ng, Aven; Tan, Alina; Li, Jinliang; Mohd-Nor, Nazeemah B.; Ng, Siok-Peng; Chew, Min-Hoe
Abstract: Purpose: COVID-19 has spread throughout the world with merciless pace. Personal protective equipment (PPE) is required to protect healthcare workers from contracting the virus. The authors evaluated the use of full-dress rehearsals (FDR) to familiarize staff with protocols and equipment that are not often use otherwise. Methods: A single institution in Singapore performed FDR with noninfected patients for endoscopy after refresher courses with PPE were conducted. FDRs were conducted between February and March 2020, during the initial phase of the COVID-19 outbreak. The FDRs involved all phases of endoscopy. Statistics from the FDRs were compared against baseline procedure statistics. A self-administered survey was conducted for the procedurists after the FDRs. Results: A total of 26 FDRs were conducted and 20 (77%) completed the survey. Among all the FDRs conducted, there was a slight increase in duration for colonoscopy FDRs (21.5 min vs 20.0 min, p = 0.22). There were no complications. All respondents had a good experience (score rating of 4-5/5). On qualitative analysis, the themes identified were: FDRs provided a good opportunity to have hands-on familiarization of the equipment on top of routine refresher training. Participants were cognizant of the ongoing outbreak and the evolving threat. Safety measures were reinforced. Procedurists who acknowledged weaknesses, requested for more training. Conclusions: Simulation training with patients provides participants with a level of realism that is critical for rapid learning. In crisis management, the most effective protocol familiarization is important to instill confidence in the PPE, workflows and healthcare partners.